Contribution of Eye-Foot Coordination and Motivation to Kicking, Passing and Stopping Skills in Players SSB Excellent in 2024: Kontribusi Kordinasi Mata-Kaki Dan Motivasi Terhadap Tendangan Keterampilan Passing Dan Stopping Pada Pemain SSB Excellent Tahun 2024 - Giovani Hendri, Alga; Rahmadani, Ahmad (Jurnal Olahraga dan Kesehatan (ORKES), 2024)
The aim of this research is to determine the contribution of eye-foot coordination and motivation to the passing and stopping results of SSB Excellent players in 2024. This type of research is multiple correlation. The population and sample in this study were SSB Excellent players in 2024, totaling 15 people with a sampling technique, namely total sampling so that the sample in this study was 15 people. The research instruments used were eye-foot coordination tests, filling out motivation questionnaires, and passing and stopping tests. The data analysis technique used is calculating the multiple correlation value. Based on the research results, it can be concluded that (1) There is a contribution of eye-foot coordination to the passing and stopping results of SSB Excellent players in 2024 amounting to 36.12%, (2) There is a contribution of motivation to the passing and stopping results of SSB Excellent players in 2024 amounting to 60, 68%, (3) There is a contribution of eye-foot coordination and motivation to the passing and stopping results of SSB Excellent players in 2024 amounting to 65.61%.